2019
DOI: 10.3389/fmicb.2018.03249
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal World: Could the Gut Mycobiome Be Involved in Neurological Disease?

Abstract: The human microbiome has received decades of attention from scientific and medical research communities. The human gastrointestinal tract is host to immense populations of microorganisms including bacteria, viruses, archaea, and fungi (the gut microbiota). High-throughput sequencing and computational advancements provide unprecedented ability to investigate the structure and function of microbial communities associated with the human body in health and disease. Most research to date has largely focused on eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 103 publications
(143 reference statements)
3
71
0
5
Order By: Relevance
“…Subsequently, the authors showed that supplementation with a probiotic Lactobacillus rhamnosus and Bifidobacterium animalis greatly improved psychiatric symptoms and normalized blood levels of C. albicans antibodies in schizophrenia [138]. A recent review by Forbes et al also describes the recent advancement in knowledge regarding gut mycobiome and the plausible role of gut mycobiota in neurological disorders [139].…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“…Subsequently, the authors showed that supplementation with a probiotic Lactobacillus rhamnosus and Bifidobacterium animalis greatly improved psychiatric symptoms and normalized blood levels of C. albicans antibodies in schizophrenia [138]. A recent review by Forbes et al also describes the recent advancement in knowledge regarding gut mycobiome and the plausible role of gut mycobiota in neurological disorders [139].…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“…In the context of PD, the gut microbiota differs from control individuals and can influence α-synuclein aggregation [37,39,40]. Accordingly, the gut microbiota in each PD patient may contribute to disease pathogenesis [36,41]. With respect to fungal infection, a connection between the mycobiota and neurodegeneration has been recently reviewed [41].…”
Section: Ivyspringmentioning
confidence: 99%
“…Although bacteria dominate microbial communities, viruses, archaea, and fungi may also play pivotal roles in maintaining the gut homeostasis [9], as evidenced by a more recent steep increase in studies assessing the role of viral and fungal components of the microbiome. However, the viral and fungal biomes remain relatively uncharacterized thus far, due to their lower abundance as well as lack of optimized tools and curated reference databases for their identification and classification [10,11].…”
Section: Introductionmentioning
confidence: 99%